Profiles of perceived social functioning in adolescent and young adult survivors of childhood cancer. Issue 8 (7th June 2020) - Willard, Victoria W.; Tillery, Rachel; Gordon, Mallorie L.; Long, Alanna; Phipps, Sean
Abstract: Objectives: Social interaction and peer relationships are critical for development, especially for adolescents and young adults (AYA). Cancer treatment may disrupt social functioning and impact quality of life. Prior research into AYA social functioning has primarily been qualitative in nature or assessed via broad measures of functioning. Given the multi‐dimensional nature of social functioning, and its importance for AYA, a person‐centered approach to analyses is needed. Methods: AYA survivors of childhood cancer, ages 13 to 23 (n = 192, 51% male) and at least 1 year post‐treatment (M = 7.35 ± 4.18 years post), completed measures to assess perceived social functioning, social support, and positive and negative affect. Caregivers also completed a measure of social functioning. Latent profile analysis was used to empirically derive profiles of perceived social functioning using the self‐perception profile for adolescents (SPPA). Results: A 3‐class solution provided the best fit to the data: 58.9% average, 33.7% high, and 7.5% low functioning. The average group reported mean scores that were similar to normative values available in the SPPA manual. Demographic and medical factors were unrelated to class membership. Social support and positive/negative affect differed significantly by class; caregiver‐ report of social functioning did not. Conclusions: Overall, the majority of AYA survivors of childhood cancer are doing well socially, with perceived adequate social functioning associated with both high levels of social support as well as greater perceptions of positive affect. Future work is needed to elucidate longitudinal trajectories of social functioning, as well as to identify and intervene with those survivors who are struggling.